2012
DOI: 10.1002/app.37690
|View full text |Cite
|
Sign up to set email alerts
|

Acrylonitrile/vinyl acetate copolymer nanofibers with different vinylacetate content

Abstract: In this study, free radical copolymerization of acrylonitrile (AN)–vinyl acetate (VAc) was performed for five different feed ratio of VAc (wt %) by using ammonium persulfate (APS) in the aqueous medium. The effect of VAc content on the spectrophotometric and thermal properties of AN–VAc copolymers was investigated by Fourier Transform Infrared–Attenuated Total Reflectance spectrophotometer (FTIR–ATR), differential scanning calorimeter (DSC), and thermal gravimetric analyzer (TGA). Thermal stability of homopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…These higher values for the copolymers in comparison with the homopolymer of AN indicated that the thermal stability of PAN was improved after it was copolymerized with VAc; this confirmed the effects of the VAc and IA functional groups in the copolymers in addition to the nitrile groups of PAN. These results were in good accordance with the literature …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…These higher values for the copolymers in comparison with the homopolymer of AN indicated that the thermal stability of PAN was improved after it was copolymerized with VAc; this confirmed the effects of the VAc and IA functional groups in the copolymers in addition to the nitrile groups of PAN. These results were in good accordance with the literature …”
Section: Resultssupporting
confidence: 93%
“…The stabilized nanofibers that contained VAc showed nearly the same weight loss behavior with P0S. These results were in good agreement with previous studies …”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations